Proceedings of the 4th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle 2007
DOI: 10.17077/drivingassessment.1241
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Driving Performance During Secondary Tasks

Abstract: Summary:Data from 36 drivers involved in a naturalistic driving study was analyzed to determine the frequency and conditions under which drivers engage in secondary behaviors and to explore the relationship these behaviors might have with driving performance. Researchers coded 1,440 five-second video clips of the drivers' faces for the occurrence of specific secondary behaviors and the duration of glances away from the forward scene. Corresponding performance data from the instrumented vehicles were used to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Results regarding gender differences with cell phone use while driving are mixed; some studies report that females are more likely to be distracted by talking on a phone, (Glassbrenner, 2005) whereas others reported men were more likely to use cell phones when driving. (Pöysti, Rajalin, & Summala, 2005; Sayer et al, 2005) Interestingly, several studies have found that gender has no effect on risk of a crash associated with phone use. (McCartt, Hellinga, & Bratiman, 2006; Pöysti et al, 2005) It remains unclear as to the exact relationship between cell phone use and distraction and how that relates to safety by gender.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results regarding gender differences with cell phone use while driving are mixed; some studies report that females are more likely to be distracted by talking on a phone, (Glassbrenner, 2005) whereas others reported men were more likely to use cell phones when driving. (Pöysti, Rajalin, & Summala, 2005; Sayer et al, 2005) Interestingly, several studies have found that gender has no effect on risk of a crash associated with phone use. (McCartt, Hellinga, & Bratiman, 2006; Pöysti et al, 2005) It remains unclear as to the exact relationship between cell phone use and distraction and how that relates to safety by gender.…”
Section: Discussionmentioning
confidence: 99%
“…(National Highway Traffic Safety Administration, 2008; JC Stutts, Reinfurt, Staplin, & Rodgman, 2001) In addition, the relative crash risk associated with specific distracting behaviors has been established using naturalistic observational study designs. (Hanowski, Perez, & Dingus, 2005; Klauer, Dingus, Neale, Sudweeks, & Ramsey, 2006; Sayer, Devonshire, & Flannagan, 2005; J Stutts et al, 2005) One measure that has received less attention is the prevalence of any distraction among drivers while driving. A handful of studies have measured the prevalence of specific types of driver distraction; however, most focused only on cell phone use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Average forward velocity was selected as an indicator of compensatory behavior, since drivers have been observed to reduce their speed to manage increasing workload (Harms, 1991;Horberry et al, 2006;Son et al, 2010). Standard deviation of lateral position is another frequently used driving performance measure (Sayer, Devonshire & Flannagan, 2007). Heart rate and skin conductance level have been shown to be useful for quantifying changes in workload prior to the occurrence of driving performance degradation (Lenneman & Backs, 2009;Mehler et al 2009;.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…For example, several studies have found that mobile phone use while driving is relatively unsafe (Caird et al, 2008;Charlton, 2009;Lamble et al, 1999). Other distractions, such as manipulating a car stereo or eating while driving have been studied naturalistically by analysis of in-car video (Klauer et al, 2014;Sayer et al, 2007). However, inattention where there is no overt external stimulus -the driver is simply not thinking about driving -has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%